1978
DOI: 10.1007/bf00254045
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and treatment of acute lymphoblastic leukemia

Abstract: The complete hematological remission (CHR) rate, duration of remission and survival were studied in relation to age, peripheral blast cell (PBC) count, presence or absence of tumor masses, cytological type, and treatment in 650 patients with acute lymphoblastic leukemia. Prognostic factors were considered separately and divided into prognostic classes. Age and PCB count correlated with both the rate and the duration of CHR. This correlation was still observed for more recent treatment schedules though it appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The demographic and haematological characteristics of the study population were in keeping with those generally reported in this disease ( Rivera et al , 1993 ; Crist et al , 1986 ; Jacquillat et al , 1978 ). In contrast, there was a higher proportion of the FAB 2 cytological type (25%, compared to 15% in general) ( Lilleyman et al , 1992 ), probably stemming from the difficulty in applying the FAB classification in multicentre surveys.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The demographic and haematological characteristics of the study population were in keeping with those generally reported in this disease ( Rivera et al , 1993 ; Crist et al , 1986 ; Jacquillat et al , 1978 ). In contrast, there was a higher proportion of the FAB 2 cytological type (25%, compared to 15% in general) ( Lilleyman et al , 1992 ), probably stemming from the difficulty in applying the FAB classification in multicentre surveys.…”
Section: Discussionsupporting
confidence: 72%
“…Major progress has been made in the management of childhood acute lymphoblastic leukaemia in the last 30 years, and most patients now survive for long periods ( Cortes & Kantarjian, 1995; Rivera et al , 1993 ; Ribeiro & Pui, 1993). Nearly 50 clinical or biological potential prognostic factors have been evaluated ( Campana & Pui, 1995; Crist et al , 1986 , 1990a, b; Fletcher et al , 1991 ; Gajjar et al , 1995 ; Gibbons et al , 1990 ; Hammond et al , 1986 ; Harbott et al , 1990 ; Hecker et al , 1994 ; Hiddeman et al , 1993 ; Jacquillat et al , 1978 ; Lennard & Lilleyman, 1989; Lilleyman et al , 1992 ; Look et al , 1985 ; McLean et al , 1996 ; Miller et al , 1983 , 1989; Neglia et al , 1988 ; Pieters et al , 1992 , 1994; Privitera et al , 1992 ; Pui et al , 1987 , 1989, 1991; Raimondi et al , 1992 ; Rautonen et al , 1988 ; Riehm et al , 1986 ; Russo et al , 1991 ; Santana et al , 1990 ; Secker‐Walker et al , 1989 ; Steinherz et al , 1991 , 1996; Uckun et al , 1995 , 1996; Wiersma et al , 1991 ). These factors are at least partly interrelated ( Hammond et al , 1986 ; Pui et al , 1988 ; Robison et al , 1980 ).…”
Section: Table I Multivariate Prognostic Studies In Childhood Allmentioning
confidence: 99%
“…Analysis of the various prognostic factors that have been referred to in patients with ALL [6,17], showed that age had no relation to response (Table I) identical to other observations [9,13,19]. All the patients with normal or low circulating leukocyte counts had a complete remission, whereas in 10 out of 15 cases (66%) with leukocytosis, complete remission occurred, and when the leukocyte counts were higher than 50,0oO/pl, the number of cases of complete remission achieved was even smaller (40 %) (Table I).…”
Section: Resultsmentioning
confidence: 99%